2019
DOI: 10.1038/s41598-019-42052-w
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris Flow Impairments in Association with Pachyvessel in Early Stages of Pachychoroid

Abstract: To analyze features of the choriocapillaris in eyes with earlier stages of pachychoroid spectrum, this study included 46 eyes with PPE, 32 age-matched eyes with pachychoroid without epitheliopathy, and 30 normal controls. Macular 3 × 3 mm 2 angiographic images were obtained with swept-source optical coherence tomography. Vascular density and signal void area in the choriocapillaris were analyzed. Topographical correlation of signal voids with the dilated choroidal large vessel (pachyvess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…This can either be attributed to a diminished but persistent shadowing artifact or alternatively hypoperfusion of the CC in patients with CSC. The latter would be in line with studies demonstrating a reduced OCTA flow in patients with CSC [ 8 , 17 , 23 , 24 ]—potentially the result of low blood flow [ 25 , 26 ], defective CC endothelial cells [ 27 , 28 ] or a thinned CC being pushed upward by pachyvessels accompanied by enlarged vascular space in Haller’s layer [ 17 , 24 , 29 , 30 ]. Nicolò et al [ 31 ] examined quantitative changes in choroidal flow areas using SS-OCTA and reported on dark patterns in the choroid regardless of the amount of fluid in CSC or in fellow eyes—anomalies not observed in healthy eyes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This can either be attributed to a diminished but persistent shadowing artifact or alternatively hypoperfusion of the CC in patients with CSC. The latter would be in line with studies demonstrating a reduced OCTA flow in patients with CSC [ 8 , 17 , 23 , 24 ]—potentially the result of low blood flow [ 25 , 26 ], defective CC endothelial cells [ 27 , 28 ] or a thinned CC being pushed upward by pachyvessels accompanied by enlarged vascular space in Haller’s layer [ 17 , 24 , 29 , 30 ]. Nicolò et al [ 31 ] examined quantitative changes in choroidal flow areas using SS-OCTA and reported on dark patterns in the choroid regardless of the amount of fluid in CSC or in fellow eyes—anomalies not observed in healthy eyes.…”
Section: Discussionsupporting
confidence: 81%
“…The x-axis describes the density of flow signal changes in the respective area, the y-axis the probability of the corresponding percentage. Note that the distributions of SD-OCTA are uniformly broader in comparison with the distribution from SS-OCTA: This hints towards a better signal-to-noise ratio from the latter imaging modality [17,24,29,30]. Nicolò et al [31] examined quantitative changes in choroidal flow areas using SS-OCTA and reported on dark patterns in the choroid regardless of the amount of fluid in CSC or in fellow eyesanomalies not observed in healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the group with pachydrusen had a thicker CT profile compared to AMD groups, which is consistent with previous studies 35 , 38 , 40 . Recent findings that pachyvessel is a general phenomenon of PSDs and pachydrusen, and that focal ischemia caused by pachyvessels affects the development of these lesions, suggests that pachydrusen may have the common pathogenesis as PSDs 5 , 14 , 40 , 41 . Indeed, the finding of the current study that eyes with pachydrusen had a greater tendency to be clustered with eyes of PSD groups than with the AMD groups with soft drusen or exudation could support this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent study showed that pachyvessels were associated with choriocapillaris flow impairment by location and size [22]. Whether the occurrence of dilated Haller pachyvessels is a primary event or secondary to the inner choroidal attenuation is still under investigation.…”
Section: 029*mentioning
confidence: 99%